Validation of an automated procedure to isolate human adipose tissue-derived cells by using the Sepax® technology - Güven, Sinan; Karagianni, Marianna; Schwalbe, Mandy; Bieback, Karen (Tissue engineering. Part C, Methods, 2012)
The stromal vascular fraction of adipose tissue has gained popularity as a source of autologous progenitor cells for tissue engineering and regenerative medicine applications. The aim of this study was to validate a newly developed, automated procedure to isolate adipose-derived mesenchymal stem/stromal cells (ASCs) from adult human lipoaspirates in a closed and clinical-grade device, based on the Sepax® technology. Using a total of 11 donors, this procedure was compared with the standard operator-based manual separation in terms of isolation yield, clonogenic fraction, phenotype, and differentiation potential of ASCs. As compared with the manual process, automation resulted in a 62% higher isolation yield, with 2.6±1.2×105 nucleated cells per mL of liposuction, and a 24% higher frequency of clonogenic progenitors. The variability in the isolation yield and clonogenicity across different preparations was reduced by 18% and 50%, respectively. The cytofluorimetric profile and in vitro differentiation capacity into mesenchymal lineages were comparable in the cells isolated using the two procedures. The new Sepax-based process thus allows an efficient isolation of ASCs with higher and more reproducible yields than the standard manual procedure, along with minimal operator intervention. These results are expected to facilitate the use of ASCs for clinical purposes, either within an intraoperative setting or in combination with further in vitro cell expansion/cultivation.